Anadromous Arctic Char, Salvelinus alpinus , Penetrating Southward on the Norwegian Coast - Jensen, John Willas (Canadian Journal of Fisheries and Aquatic Sciences, 1981)
Anadromous Arctic char, Salvelinus alpinus, have been limited on the Norwegian coast to areas north of 65°N. In 1967 anadromous char invaded the river Granvinelv in the Hardangerfjord at 60°N, and have given rise to a dense population of stationary freshwater char in the lake Granvinvatn. During 1978–79 anadromous char spread to several rivers at the head of the fjord. Events assumed to have taken place during the melting-off phase of the last glacial period are recurring. The Hardangerfjord is colder than the outside coastal waters and will very probably function as a subarea of the char. The available data indicates that an average coastal water temperature of 14 °C at 4–5 m depth is limiting the anadromous char to the south on the Norwegian coast. Continuous water masses colder than 13.6 °C could have permitted the southward penetration of anadromous char to the Hardangerfjord in 1964, but the char may also have escaped from a hatchery in the vicinity of the fjord. Landlocked char of a river entering the head of the Hardangerfjord evidently do not possess the capacity to give rise to an anadromous population.Key words: Salvelinus alpinus, anadromous char, distribution area, southward penetration, temperature barrier